2020
DOI: 10.1016/j.enbuild.2020.109758
|View full text |Cite
|
Sign up to set email alerts
|

Improvement to EN ISO 52016-1:2017 hourly heat transfer through a wall assessment: the Italian National Annex

Abstract: Energy efficiency in buildings is a crucial topic to reduce the worldwide energy consumptions and fight the climate change. A key aspect is the assessment of the heat transfer through the opaque elements of the building envelope. One way to do it is modelling the element as a resistors and capacitors network (RC), using the thermal-electrical analogy. In the hourly dynamic method introduced by the recently published standard EN ISO 52016-1:2017, each opaque element is modelled with a RC-network. Italy has impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…This approach allowed the authors to detect the use of constant surface heat transfer coefficients as the main cause of deviation in the outcomes. The effect of single assumptions on the simulation results have been so far investigated by Mazzarella et al [21]. The authors applied an analytical single process approach for the validation of the EN ISO 52016-1 conduction heat transfer model and of an improved version of this, introduced in the Italian National Annex of the standard.…”
Section: Validation Studies Of the En Iso 52016-1 Hourly Modelmentioning
confidence: 99%
“…This approach allowed the authors to detect the use of constant surface heat transfer coefficients as the main cause of deviation in the outcomes. The effect of single assumptions on the simulation results have been so far investigated by Mazzarella et al [21]. The authors applied an analytical single process approach for the validation of the EN ISO 52016-1 conduction heat transfer model and of an improved version of this, introduced in the Italian National Annex of the standard.…”
Section: Validation Studies Of the En Iso 52016-1 Hourly Modelmentioning
confidence: 99%
“…Advances in Civil Engineering standard model. Nonetheless, it provides variables and calculation formula for evaluating energy performance in buildings [34][35][36][37]. In particular, it is possible to calculate the heating and cooling loads using the time and monthly calculation method.…”
Section: Consideration Of International Standard Model Variablesmentioning
confidence: 99%
“…To improve the current calculation method, a new and more accurate approach is provided by the EN 52016 [28], consisting of an hourly energy-calculation procedure capable of accounting for the thermal inertia of buildings' envelopes. As this new methodology is quite recent, few studies are yet found in the literature, though one such [29][30][31][32][33] performed the first energy-analysis approach based on EN 52016.…”
Section: Introductionmentioning
confidence: 99%
“…According to Annex B of the UNI EN 52016 standard, each building envelope is modelled with five nodes (plus two nodes related to indoors and outdoors), interconnected by four thermal resistances (in addition to the ones related to radiative and convective resistances) and from one to five capacitances [28,33].…”
mentioning
confidence: 99%